2013
DOI: 10.1080/15226514.2012.723070
|View full text |Cite
|
Sign up to set email alerts
|

Field Evaluation of Willow Under Short Rotation Coppice for Phytomanagement of Metal-Polluted Agricultural Soils

Abstract: Short rotation coppice (SRC) of willow and poplar might be a promising phytoremediation option since it uses fast growing, high biomass producing tree species with often a sufficient metal uptake. This study evaluates growth, metal uptake and extraction potentials of eight willow clones (Belders, Belgisch Rood, Christina, Inger, Jorr, Loden, Tora and Zwarte Driebast) on a metal-contaminated agricultural soil, with total cadmium (Cd) and zinc (Zn) concentrations of 6.5 +/- 0.8 and 377 +/- 69 mg kg(-1) soil, res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
34
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 66 publications
(36 citation statements)
references
References 44 publications
2
34
0
Order By: Relevance
“…For the latter, clones can be grown for specific SRC purposes and then imported and planted at their final destination areas [12,15]. Moreover, it has been observed that the inclusion of native species in SRC plantations can increase the biodiversity and the supply of ecosystem services at regional scale [16][17][18], allowing an effective phytoremediation of metalcontaminated areas [19][20][21][22][23]. Hence, solutions exist to provide synergic ecological benefits to the main energy-oriented goal of the SRC.…”
Section: Introductionmentioning
confidence: 99%
“…For the latter, clones can be grown for specific SRC purposes and then imported and planted at their final destination areas [12,15]. Moreover, it has been observed that the inclusion of native species in SRC plantations can increase the biodiversity and the supply of ecosystem services at regional scale [16][17][18], allowing an effective phytoremediation of metalcontaminated areas [19][20][21][22][23]. Hence, solutions exist to provide synergic ecological benefits to the main energy-oriented goal of the SRC.…”
Section: Introductionmentioning
confidence: 99%
“…In the last decade, the use of agro-forestry practices such as short rotation coppice (SRC) with high biomass producing tree clones has attracted great attention by HMCS owners, managers and policy makers because it can combines bioenergy production, risks attenuation, and restoration of soil fertility and ecosystem services (van Slycken et al, 2013b). Fast growing woody plants such as Eucalyptus sp., Populus spp.…”
Section: Introductionmentioning
confidence: 99%
“…Taking into consideration (i) that the metal accumulation capacity of various clones of plants of the same species can be significantly different (Table ; Van Slycken et al ., ) and (ii) that plant‐associated bacteria play an important role during metal phytoextraction (Weyens et al ., ,c), the question arises if the differences in metal accumulation capacity between these clones might, at least partly, be related to differences in their associated bacterial population.…”
Section: Introductionmentioning
confidence: 99%